PENGAWASAN PEJABAT PEMBUAT AKTA TANAH OLEH MAJELIS PEMBINA DAN PENGAWAS PPAT DAERAH DI KABUPATEN AGAM - Paramitha, Nadya; Warman, Kurnia; Andora, Hengki (UNES Law Review, 2023)
Supervision of PPAT by the Regional PPAT Advisory and Supervisory Board in Agam Regency is carried out based on the Regulation of the Minister of Agrarian Affairs and Spatial Planning / Head of the National Land Agency Number 2 of 2018 (Permen ATR / BPN), supervision of the implementation of PPAT positions, this is carried out at least once a year. The forms of violations committed by the PPAT in Agam Regency based on the results of Supervision by the MPPD PPAT Agam Regency can be grouped based on 2 categories, namely violations related to the attributes of the PPAT in carrying out such as violations of rules related to the PPAT stamp. Violation for not being notified in writing of changing office address, Violation because there is no guest book and attendance list of PPAT and employees. The second category is violations related to the deed in the form of violations because there is no deed formula, violations because there is no numbering in the deed book, there are no numbers and names in the volume of the document, violations because there is no photo evidence when committing the violation of the deed and violations because the deed does not comply with Article 26 PP No. 37 of 1998 concerning PPAT, and violations because the deed has not been bound and bundled. The findings obtained at the inspected PPAT office will be included in the inspection problem, which also provides an inspection